Late pacemaker implantation after atrioventricular nodal reentrant tachycardia ablation: A systematic review and meta‐analysis. (30th September 2022) - Sim, Ming G.; Chan, Siew P.; Kojodjojo, Pipin; Tan, Eugene S. J.
Abstract: Introduction: Catheter ablation (CA) of atrioventricular nodal reentrant tachycardia (AVNRT) is associated with late pacemakers for AV block (AVB). We performed a systematic review and meta‐analysis of the pooled incidence of late pacemakers for AVB after CA of AVNRT. Methods and Results: Relevant studies were identified from four electronic databases (PubMed, EMBASE, Scopus, and Cochrane Trial Register) from inception to 2022. A random effects model was used to calculate the odds of late pacemakers in CA of AVNRT compared to atrioventricular reentrant tachycardia (AVRT). Of 533 articles screened, 13 were included in systematic review. CA for AVNRT was performed in 16 471 patients (mean age 54 ± 17 years, 63% females), of which 68 (0.4%) underwent pacemaker implantation for late AVB. Meta‐analysis was performed in 5 of the 13 studies (mean follow‐up duration 7 ± 4 years). Patients who underwent CA of AVNRT were older (58 ± 17 vs. 52 ± 20 years, p  < .001), and more likely female (60% vs. 41%, p  < .001) than AVRT. Pooled estimates of late pacemakers for AVB were higher in CA of AVNRT than AVRT (0.5% vs. 0.2%, p  = .006), with CA in AVNRT associated with almost twofold increased odds of late pacemakers indicated for AVB (odds ratio: 1.94, 95% confidence interval: 1.08–3.47, p  = .027) compared to AVRT. Conclusion: AVNRT ablation is safe but associated with a low but definitely increased risk of requiring pacing in the later years due to AVB. This association is confirmed by pooling over 16 000 AVNRT patients receiving clinically indicated ablation and is helpful in providing informed consent for prospective patients undergoing ablation for AVNRT.